PENGARUH KOMITMEN ORGANISASI, PERAN KEPEMIMPINAN, MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJAPEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BINJAI. - Viska Yanti (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The problem in this research is: how the influence of organizational commitment on employee performance at the Binjai Pratama Tax Office. How does the role of leadership influence employee performance, how does motivation influence employee performance, how does job satisfaction affect employee performance, how does organizational commitment influence, role leadership, motivation and job satisfaction on employee performance at the Binjai Pratama Tax Office. The hypothesis proposed is: Organizational commitment has a positive and significant effect on employee performance, the role of leadership has a positive and significant effect on employee performance, motivation has a positive and significant effect on employee performance, job satisfaction has a positive and significant effect on employee performance, organizational commitment, leadership role, motivation and job satisfaction have a positive and significant effect on employee performance at the Binjai Pratama Tax Office ..